Analysis of the Difficulties in Teaching Arabic Language to Students: Field Study at "Sarj Al-Huda" Islamic Primary School, East Jakarta - Muhammad Qadhafi; Niken Sundari; Taufik Hidayat; Tahir Wijaya; Soraiya Mohammad Usman (Al-Muyassar: Journal of Arabic Education, 2026)
This research aims to describe the difficulties faced by sixth-grade students at Sirojul Huda Islamic Elementary School in East Jakarta in learning Arabic, to identify the factors influencing these difficulties, and to propose appropriate solutions to overcome them. The research employed a descriptive qualitative approach supported by a questionnaire. Data was collected through observation, interviews, documentation, and the questionnaire itself. This methodology allowed the researcher to gain a comprehensive understanding of the educational reality and the challenges students face in learning Arabic. The research findings revealed that students encounter a range of linguistic and non-linguistic difficulties. The linguistic difficulties included a weak command of Arabic vocabulary, difficulty speaking Arabic, and a limited ability to understand some grammatical rules. The non-linguistic difficulties included limited opportunities for practice and training, weak motivation to learn, and certain aspects of the teaching methods and educational resources used. These results indicate that difficulties in learning Arabic are not solely related to linguistic factors but are also influenced by psychological, educational, and environmental factors surrounding the learners. To address these difficulties, the study recommends developing teaching methods to be more interactive and engaging, providing greater opportunities to practice the Arabic language inside and outside the classroom, enhancing students’ motivation and self-confidence, in addition to employing diverse educational tools that contribute to the development of various language skills.